COVID-19 impact on the decision process of the Italian Medicine Agency: a quantitative assessment - Beatrice Canali; Laura Candelora; Francesca Fiorentino; Tom Halmos; Paola La Malfa; Francesca Massara; Chiara Vassallo; Duccio Urbinati (Global & Regional Health Technology Assessment, 2023)
Background: Since the COVID-19 pandemic has placed more attention on drugs’ approval process and the importance of rapid decision-making in the healthcare sector, it is crucial to assess how time to market (TTM) of drugs varied.